Detection of natural occurrence of Tritrichomonas foetus in cats in Araçatuba, São Paulo, Brazil - Duarte, Roberta P. [UNESP]; Rocha, Paulo Ricardo D.A. [UNESP]; Nakamura, Alex A. [UNESP]; Cipriano, Rafael S.; Viol, Milena A.; Melo, Guilherme D.; Meireles, Marcelo V. [UNESP]; Machado, Gisele F. [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to investigate the occurrence of Tritrichomonas foetus in cats in the area surrounding the city of Araçatuba municipality, State of São Paulo, Brazil. Fecal samples from 129 cats were collected by rectal flush technique. It was compared two diagnosis methods, direct examination of feces and PCR. The presence of T. foetus DNA was verified using PCR by amplification of 347-bp fragment from the primers TFR3 and TFR4 and amplicons of positive cases were sequenced. Statistical analyses were performed investigating the associations between T. foetus infection with gender, age, breed, presence of diarrhea and/or history of diarrhea, previous treatment, lifestyle, origin, environment, and co-infection. T. foetus was observed in one sample (n=129) by direct microscopic examination of feces while PCR was positive in five samples (3.9%). Giardia species and Cryptosporidium species co-infection was also observed. Statistical analyses showed no significant associations between T. foetus infection and all listed factors, although most positive cats were asymptomatic and lived in multi-cat household. The isolates of T. foetus showed 100% identical sequences with other T. foetus isolates from cats around the world. So, the occurrence of T. foetus was confirmed in cats in Araçatuba city (Brazil). This parasite must be considered as a differential diagnosis in cats with diarrhea and also in asymptomatic carriers as source of infection in multi-cat environments.
Keywords: Cats; Diarrhea; Genetic sequencing; Parasitoses; PCR; Polymerase chain reaction; Tritrichomonas foetus